Nasal carriage of Methicillin-resistant Staphylococcus aureus among healthy population of Kashmir, India - Fomda, BA; Thokar, MA; Khan, A; Bhat, JA; Zahoor, D; Bashir, G; Majid, A; Ray, P (Indian journal of medical microbiology, 2014)
Background: Nasal colonisation with community acquired methicillin resistant Staphylococcus aureus (CA-MRSA) is being increasingly reported, especially in places where people are in close contact and where hygiene is compromised. The aim of this study was to find out prevalence of methicillin resistant S.aureus (MRSA) colonising anterior nares of healthy subjects. Materials and Methods: Nasal swabs of healthy subjects were collected aseptically and cultured using standard microbiological protocols. Antibiotic susceptibility was done by Kirby-Bauer disc diffusion method according to CLSI guidelines. Methicillin resistance was detected by cefoxitin disc diffusion method and confirmed by minimum inhibitory concentration (MIC) and amplification of mecA gene by PCR. Strain typing of MRSA strains was done by PFGE. Results: Out of 820 samples, S.aureus was isolated from 229 (27.92%) subjects. Of the 229 isolates, 15 were methicillin resistant. All S. aureus isolates were susceptible to vancomycin. Nasal carriage of MRSA was found to be 1.83% among healthy population. The isolates were found to be polyclonal by PFGE analysis. Conclusion: High prevalence of MRSA is a cause of concern and strategies to interrupt transmission should be implemented.